2018
DOI: 10.1186/s13098-018-0350-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary protein intake and type 2 diabetes varies by dietary pattern

Abstract: BackgroundEpidemiological studies have demonstrated that high total protein intake was related to type 2 diabetes mellitus (T2DM) risks. However, few studies considered the impact of dietary pattern.ObjectiveWe examined the associations between protein intake and T2DM in different dietary patterns.MethodsWe used the demographic and dietary information of adults aged 18–75 years from the China Health and Nutrition Survey (2009), consisting of 4113 women and 4580 men. Dietary data was collected by using 24-h rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 46 publications
3
25
1
2
Order By: Relevance
“…Protein content of the vegetable sauces was consistent with Sabitha et al [24]; Ukegbu and Okebugwu [25] and Davidson et al [22]. Protein diets especially plant based has been shown to promote glucose homeostasis and is not associated with T2DM risk [26,27] but animal protein especially red and processed meat promotes insulin resistance and increases gluconeogenesis [28].…”
Section: Proximate Dietary Fibre and Energy Composition Of Vegetablesupporting
confidence: 79%
“…Protein content of the vegetable sauces was consistent with Sabitha et al [24]; Ukegbu and Okebugwu [25] and Davidson et al [22]. Protein diets especially plant based has been shown to promote glucose homeostasis and is not associated with T2DM risk [26,27] but animal protein especially red and processed meat promotes insulin resistance and increases gluconeogenesis [28].…”
Section: Proximate Dietary Fibre and Energy Composition Of Vegetablesupporting
confidence: 79%
“…legumes) was associated with decreased risk of T2DM, on the contrary to higher intake of protein from animal sources (e.g. red meat) [39]. Same authors emphasized the importance of focusing on dietary patterns, rather than individual macronutrients.…”
Section: Meat Fish Eggsmentioning
confidence: 99%
“…Group E has a good pancreatic profile because A4B1C3 rice has high dietary fiber and protein content. Protein is an important modulator in glucose homeostasis by increasing gluconeogenesis and preventing insulin resistance [21]. Research conducted by [22] showed a synergistic effect when people with type 2 diabetes consume glucose with protein in increasing insulin stimulation so that insulin concentration increases compared to just consuming glucose.…”
Section: Pancreatic Histopathologymentioning
confidence: 99%